A method for separating and recovering chromium from a chromium-containing dust powder produced in the smelting of metallic chromium

CN122979643APending Publication Date: 2026-10-27JINZHOU JIXIN PYROMATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611487306.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明的目的在于:提供了一种从金属铬冶炼含铬收尘粉中分离回收铬的方法,以解决现有针铁矿法除铁过程中因铬共沉淀损失导致铬总回收率低的问题

Benefits of technology

[0025]1.本发明通过改性γ-聚谷氨酸与改性纳米海泡石纤维分别从体相螯合锁定与固液界面晶面调控两个环节共同抑制Cr3+共沉淀损失,改性γ-聚谷氨酸在除铁前将Cr3+转化为动力学稳定的可溶性配合物,从源头减少进入除铁体系的游离Cr3+,改性纳米海泡石纤维通过抑制FeOOH晶体生长速率、减少表面活性吸附位点,对残余游离Cr3+形成界面拦截,二者协同解决了现有针铁矿法除铁过程中因铬共沉淀损失导致铬总回收率低的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979643A_ABST
    Figure CN122979643A_ABST
Patent Text Reader

Abstract

The application discloses a method for separating and recovering chromium from chromium-containing dust collecting powder in metal chromium smelting, and belongs to the technical field of hydrometallurgy, and comprises the following steps: S1, sulfuric acid leaching and reduction; S2, chelation pretreatment; S3, iron removal by oxidation; and S4, decomplexation recovery; the application realizes common inhibition of Cr 3+ Co-precipitation loss, and the two solve the problem of low total chromium recovery rate caused by chromium co-precipitation loss in the existing goethite method iron removal process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hydrometallurgical technology, specifically relating to a method for separating and recovering chromium from chromium-containing dust collected during chromium smelting. Background Technology

[0002] Chromium-containing dust produced during chromium smelting is leached with sulfuric acid, and the resulting leachate contains the target metal Cr. 3+ It also contains impurity iron ions (in the form of Fe). 2+ and Fe 3+ (Coexistence of forms). To obtain high-purity chromium products, the leaching solution needs to undergo an iron removal process to remove iron in solid form. Industrially, the goethite method is commonly used: first, an oxidant is used to remove Fe... 2+ Oxidized to Fe 3+ Then slowly add a neutralizing agent to adjust the pH of the system, so that Fe 3+ Hydrolysis produces FeOOH precipitate, achieving solid-liquid separation of iron and chromium.

[0003] The iron removal process described above is accompanied by the co-precipitation loss of chromium. Cr 3+ with Fe 3+ The six-coordinate ions have similar radii and charges, and their hydrated ions and hydroxyl complexes are structurally similar. This is because Cr... 3+ The structural basis for the ability to co-precipitate with FeOOH and form a (Fe,Cr)OOH solid solution. This loss mainly occurs through two pathways: first, the newly formed FeOOH precipitate has a large specific surface area and abundant surface hydroxyl groups, which affects the Cr in the solution. 3+ It has strong surface adsorption and coordination trapping capabilities; secondly, Cr 3+ FeOOH crystals can be inserted into lattice sites to replace Fe during crystal growth. 3+ This forms a chemically bonded and stable solid solution. Such bonds are difficult to desorb by conventional water washing and acid washing, and the resulting chromium loss has a significant impact on the recovery rate.

[0004] Existing goethite processes lack the ability to process Cr. 3+ Selective suppression of coprecipitation is difficult because surface adsorption and lattice substitution are two separate loss mechanisms that cannot be simultaneously suppressed by a single method. Therefore, how to specifically suppress these two coprecipitation loss pathways and improve the overall chromium recovery rate while ensuring iron removal efficiency is a pressing technical problem in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a method for separating and recovering chromium from chromium-containing dust collected during chromium smelting, in order to solve the problem of low total chromium recovery rate caused by chromium co-precipitation loss in the existing goethite iron removal process.

[0006] The technical solution adopted in this invention is as follows: A method for separating and recovering chromium from chromium-containing dust collected during chromium smelting, comprising the following steps:

[0007] S1. Sulfuric acid leaching and reduction: Mix chromium dust collected from chromium smelting with 20-30 wt% sulfuric acid solution at a solid-liquid ratio of 1:4-8 (unit: g / mL). Leach at 85-95℃ for 2-4 hours. After leaching, filter while hot to obtain leachate 1. Add 30-32 wt% NaOH solution to leachate 1 to adjust the pH to 2.0-3.0, then add a reducing agent and react at 40-60℃ for 0.5-1 hours to obtain leachate 2.

[0008] S2, Chelation pretreatment: Add modified γ-polyglutamic acid to leachate 2 and stir the reaction at 60-80℃ for 3-5 hours to obtain treatment solution 1;

[0009] S3. Iron removal by oxidation: Add 25-35 wt% hydrogen peroxide solution to treatment solution 1 and react at 35-40℃ for 0.5-1 hour to obtain an oxidizing solution; heat the oxidizing solution to 60-80℃, add modified nano-sepiolite fiber, stir for 10-30 minutes, then add a neutralizing agent at a rate of 0.5-1.0 mL / min, adjust the pH to 3.0-4.0, and react at 60-80℃ for 1.5-2 hours to obtain treatment solution 2.

[0010] S4. Complex Removal and Recovery: Filter the treated liquid 2 to obtain filter residue and filtrate. Add 90-98 wt% sulfuric acid to the filtrate to adjust the pH to less than 1. Transfer the filtrate to a sealed, pressure-resistant container and maintain the temperature at 130-150℃ for 1-2 hours to obtain a product containing free Cr. 3+ Chromium recovery solution.

[0011] Further, the Cr in the leachate 1 described in step S1 3+ Concentration of 20-35 g / L, Fe 2+ Concentration of 5-15 g / L, Fe 3+ The concentration is 2-8 g / L; the Cr in the leachate 2 3+ Concentration of 20-35 g / L, Fe 2+ Concentration of 7-22 g / L, Fe 3+ Concentration less than 0.5 g / L.

[0012] Furthermore, the reducing agent mentioned in step S1 is ascorbic acid, and the amount added is 4-20 g / L.

[0013] Furthermore, the preparation method of the modified γ-polyglutamic acid includes the following steps:

[0014] A1. Dissolve γ-polyglutamic acid in deionized water, adjust the pH to 6-7 with 5wt% NaOH solution, add EDC hydrochloride, stir at room temperature to obtain an activation solution, add the activation solution dropwise to 5-10wt% ethylenediamine aqueous solution under ice bath conditions of 0-5℃, dialyze to remove unreacted ethylenediamine after the reaction is complete to obtain an intermediate solution;

[0015] A2. Adjust the pH of the intermediate solution obtained in step A1 to 9-10 with 5wt% NaOH solution, add chloroacetic acid, and react at 50-60℃ for 4-6 hours. After the reaction is completed, dialyze the reaction solution with deionized water to obtain an iminodiacetic acid-grafted γ-polyglutamic acid solution.

[0016] A3. The pH of the iminodiacetic acid-grafted γ-polyglutamic acid solution obtained in step A2 was adjusted to 6-7 with 5wt% NaOH solution. EDC hydrochloride and NHS were added, followed by amino-polyethylene glycol. The mixture was stirred and reacted at room temperature, dialyzed, and freeze-dried to obtain modified γ-polyglutamic acid.

[0017] Furthermore, the preparation method of the modified nano-sepiolite fibers includes the following steps:

[0018] B1. Nano-sized sepiolite fibers with a diameter of 20-50 nm were vacuum dried at 120 °C for 12 hours. After removal, they were dispersed in anhydrous toluene, and diethylphosphonoethyltriethoxysilane was added. The mixture was refluxed at 80 °C for 8-12 hours under nitrogen protection. After centrifugation, the supernatant was discarded, and the mixture was washed with toluene and ethanol in sequence. After ultrasonic dispersion, it was centrifuged again to obtain diethylphosphonate-grafted sepiolite.

[0019] B2. Disperse the diethyl phosphonate-grafted sepiolite obtained in step B1 in dichloromethane, add trimethylsilane bromide, stir the reaction at room temperature, remove the solvent by rotary evaporation after the reaction is complete, add anhydrous methanol and continue stirring the reaction, centrifuge, wash and dry to obtain phosphonate-modified sepiolite.

[0020] B3. Disperse the phosphonic acid-modified sepiolite obtained in step B2 in anhydrous toluene, add 3-aminopropyltriethoxysilane, reflux at 80°C for 6-8 hours under nitrogen protection, centrifuge, wash, and then disperse in N,N-dimethylformamide, add succinic anhydride, stir and react at room temperature, centrifuge, wash, and dry to obtain modified nano-sepiolite fibers.

[0021] Further, the amount of modified γ-polyglutamic acid added in step S2 is 8-12 g / L; the amount of modified nano-sepiolite fiber added in step S3 is 0.8-1.2 g / L.

[0022] Further, the neutralizing agent mentioned in step S3 is added dropwise in the form of a slurry with a mass fraction of 10%-20%, and the neutralizing agent is lime milk, with an addition amount of 20-40 g / L calculated as Ca(OH)2.

[0023] Furthermore, in step S3, FeOOH seed crystals are added before adding the neutralizing agent, and the amount added is 0.05-0.3 g / L.

[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0025] 1. This invention inhibits Cr from two aspects: bulk chelation and locking, and solid-liquid interface crystal plane regulation, by modifying γ-polyglutamic acid and modified nano-sepiolite fibers respectively. 3+ Coprecipitation loss, modified γ-polyglutamic acid removes Cr before iron removal 3+ It is transformed into a kinetically stable soluble complex, thereby reducing the amount of free Cr entering the iron removal system at the source. 3+ Modified nano-sepiolite fibers inhibit the growth rate of FeOOH crystals and reduce surface active adsorption sites, thereby reducing the free Cr content. 3+ By forming an interface interception, the two work together to solve the problem of low total chromium recovery rate caused by chromium co-precipitation loss in the existing goethite iron removal process.

[0026] 2. Both modified substances described in this invention can be directly added in stages based on the existing goethite iron removal process, without changing the main process flow and equipment, nor changing the rigid usage requirements of oxidant and neutralizer; after the process is completed, the two modified substances are degraded with the decomposition filtrate and discharged with the iron slag, respectively, without requiring separation and recovery. While improving the chromium recovery rate, it also has good industrial adaptability and process simplicity. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 This is a flowchart illustrating a method for separating and recovering chromium from chromium-containing dust collected during chromium smelting in this embodiment. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, and not all embodiments. The components of the embodiments of the invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0030] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.

[0031] It should be noted that relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0032] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0033] Example 1: This example provides a method for separating and recovering chromium from chromium-containing dust collected during chromium smelting, comprising the following steps:

[0034] S1. Sulfuric acid leaching and reduction: Take 100g of chromium dust collected from metallic chromium smelting and mix it with a 25wt% sulfuric acid solution at a solid-liquid ratio of 1:6 (g / mL), i.e., add 600mL of sulfuric acid solution and leach at 90℃ for 3 hours. After leaching, filter while hot to obtain leachate 1; add a 31wt% NaOH solution to leachate 1 to adjust the pH to 2.5, then add a reducing agent and react at 50℃ for 45 minutes to obtain leachate 2.

[0035] S2, Chelation pretreatment: Modified γ-polyglutamic acid was added to leachate 2 and stirred at 70°C for 4 hours to obtain treatment solution 1;

[0036] S3, Oxidation to remove iron: Add 30wt% hydrogen peroxide solution (25g / L) to treatment solution 1 and react at 37℃ for 1 hour to obtain an oxidizing solution; heat the oxidizing solution to 70℃, add modified nano-sepiolite fibers, and stir for 20 minutes; then add a neutralizing agent at a rate of 0.75mL / min, adjust the pH to 3.5, and react at 70℃ for 1.5 hours to obtain treatment solution 2;

[0037] S4. Complex Removal and Recovery: The treated liquid 2 is filtered to obtain filter residue and filtrate. 95 wt% sulfuric acid is added to the filtrate to adjust the pH to 0.8. The solution is then transferred to a sealed, pressure-resistant container and maintained at 140°C for 1.5 hours to obtain a product containing free Cr. 3+ Chromium recovery solution.

[0038] In step S1, the Cr in the leachate 1 3+ The concentration is 28 g / L, Fe 2+ The concentration is 10 g / L, Fe 3+ The concentration is 5 g / L; the Cr in the leachate 2 3+ The concentration is 28 g / L, Fe 2+ The concentration was 14.7 g / L, Fe 3+ The concentration is 0.3 g / L.

[0039] The reducing agent mentioned in step S1 is ascorbic acid, and the amount added is 10g / L.

[0040] The preparation method of the modified γ-polyglutamic acid includes the following steps:

[0041] A1. Dissolve 10g of γ-polyglutamic acid in 101mL of deionized water, adjust the pH to 6.5 with 5wt% NaOH solution, add 4.0g of EDC hydrochloride, and stir at room temperature for 1 hour to obtain the activated solution; Separately, prepare an ethylenediamine aqueous solution by adding 9.3g of ethylenediamine to 107mL of deionized water. Under ice bath conditions of 0℃, add the activated solution dropwise to the ethylenediamine aqueous solution at a rate of 0.8mL / min. After the addition is complete, continue stirring at 0℃ for 2 hours. After the reaction is complete, put the reaction solution into a dialysis bag with a molecular weight cutoff of 3500Da and dialyze it in deionized water for 48 hours, changing the solution every 6 hours to obtain the intermediate solution.

[0042] A2. Adjust the pH of the intermediate solution obtained in step A1 to 9.5 with 5wt% NaOH solution, add 5.9g of chloroacetic acid, and react in a 55℃ water bath for 5 hours. After the reaction is completed, put it into a dialysis bag with a molecular weight cutoff of 3500 Da, and dialyze it in deionized water for 48 hours, changing the water every 6 hours to obtain an iminodiacetic acid-grafted γ-polyglutamic acid solution.

[0043] A3. The γ-polyglutamic acid grafted with iminodiacetic acid obtained in step A2 was adjusted to pH 6.5 with 5wt% NaOH solution. 1.5g of EDC hydrochloride and 0.74g of NHS were added, and the mixture was stirred at room temperature for 1 hour. 6.4g of amino-polyethylene glycol (H2N-PEG-OCH3, molecular weight 1000) was added, and the mixture was stirred at room temperature for 12 hours. After the reaction was completed, the mixture was placed in a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed in deionized water for 48 hours, with the water changed every 6 hours. After dialysis, the mixture was pre-frozen at -40℃ for 12 hours and then transferred to a freeze dryer. It was freeze-dried at a vacuum of less than 10 Pa and a temperature of -40℃ for 24 hours to obtain modified γ-polyglutamic acid.

[0044] The preparation method of the modified nano-sepiolite fiber includes the following steps:

[0045] B1. Take 10g of 30nm diameter sepiolite nanofibers, vacuum dry them at 120℃ for 12 hours, then disperse them in 125mL of anhydrous toluene, add 3.0g of diethylphosphonoethyltriethoxysilane, and reflux at 80℃ for 10 hours under nitrogen protection. After the reaction is completed, centrifuge at 8000rpm for 10 minutes, discard the supernatant, wash twice with toluene and ethanol (50mL each time), sonicate for 5 minutes, and centrifuge at 8000rpm for 10 minutes to obtain diethylphosphonate-grafted sepiolite.

[0046] B2. Disperse all the phosphonate-modified sepiolite obtained in step B1 in 100 mL of dichloromethane, add 12.4 g of trimethylsilane bromide, stir at room temperature for 24 hours, remove the solvent by rotary evaporation after the reaction is complete, add 50 mL of anhydrous methanol, continue stirring for 1 hour, centrifuge at 8000 rpm for 10 minutes, wash twice with methanol and deionized water (50 mL each time), and dry under vacuum at 60 °C for 8 hours to obtain phosphonate-modified sepiolite.

[0047] B3. Disperse all the phosphonic acid-modified sepiolite obtained in step B2 in 125 mL of anhydrous toluene, add 1.55 g of 3-aminopropyltriethoxysilane, and reflux at 80 °C for 7 hours under nitrogen protection. After the reaction is complete, centrifuge at 8000 rpm for 10 minutes, wash twice with toluene and ethanol (50 mL each time), then disperse in 100 mL of N,N-dimethylformamide, add 1.40 g of succinic anhydride, stir and react at room temperature for 12 hours, centrifuge at 8000 rpm for 10 minutes, wash twice with N,N-dimethylformamide and deionized water (50 mL each time), and vacuum dry at 60 °C for 8 hours to obtain modified nano-sepiolite fibers.

[0048] The amount of modified γ-polyglutamic acid added in step S2 is 10 g / L; the amount of modified nano-sepiolite fiber added in step S3 is 1.0 g / L.

[0049] The neutralizing agent mentioned in step S3 is added dropwise in the form of a slurry with a mass fraction of 15%. The neutralizing agent is lime milk, and the amount added is 33 g / L based on Ca(OH)2.

[0050] In step S3, FeOOH seed crystals are added before the neutralizing agent is added, and the amount added is 0.2 g / L.

[0051] Example 2: This example differs from Example 1 in that the amount of modified γ-polyglutamic acid added in step S2 is 8 g / L; and the amount of modified nano-sepiolite fiber added in step S3 is 0.8 g / L. The rest is the same as in Example 1.

[0052] Example 3: This example differs from Example 1 in that the amount of modified γ-polyglutamic acid added in step S2 is 12 g / L; and the amount of modified nano-sepiolite fiber added in step S3 is 1.2 g / L. The rest is the same as in Example 1.

[0053] Comparative Example 1: This comparative example differs from Example 1 in that it uses unmodified γ-polyglutamic acid instead of modified γ-polyglutamic acid. The amount added, reaction temperature, and reaction time are the same as in Example 1. The rest is the same as in Example 1.

[0054] Comparative Example 2: This comparative example differs from Example 1 in that the modified γ-polyglutamic acid was prepared only according to steps A1 and A2. The iminodiacetic acid-grafted γ-polyglutamic acid solution obtained in step A2 was directly freeze-dried (freeze-drying conditions were the same as in step A3) to obtain iminodiacetic acid-grafted γ-polyglutamic acid solid, without performing step A3. The amount of solid added, the reaction temperature, and the reaction time were the same as those in the modified γ-polyglutamic acid of Example 1. The rest was the same as in Example 1.

[0055] Comparative Example 3: This comparative example differs from Example 1 in that it uses unmodified nano-sepiolite fibers (30 nm in diameter, the same as the raw materials used before modification in Example 1) instead of modified nano-sepiolite fibers, and the amount added is the same as in Example 1. The rest is the same as in Example 1.

[0056] Comparative Example 4: This comparative example differs from Example 1 in that the modified nano-sepiolite fibers in this example only undergo steps B1 and B2 to prepare phosphonic acid-modified sepiolite, without the 3-aminopropyltriethoxysilane grafting and succinic anhydride acylation treatment in step B3. The amount of phosphonic acid-modified sepiolite added is the same as that in the modified nano-sepiolite fibers of Example 1. The rest is the same as in Example 1.

[0057] Comparative Example 5: This comparative example differs from Example 1 in that modified γ-polyglutamic acid is not added in step S2, and the leachate 2, after reduction treatment, does not undergo chelation pretreatment and directly enters step S3 for iron removal oxidation. The amounts and steps of the remaining components are the same as in Example 1.

[0058] Comparative Example 6: This comparative example differs from Example 1 in that modified nano-sepiolite fibers are not added in step S3. The amounts and steps of the remaining components are the same as in Example 1.

[0059] Comparative Example 7: This comparative example differs from Example 1 in that FeOOH seed crystals are not added before adding the neutralizing agent in step S3. The amounts and steps of the remaining components are the same as in Example 1.

[0060] Comparative Example 8: This comparative example differs from Example 1 in that, in step S3, modified nano-sepiolite fibers are not added. Instead, after pressure filtration in step S4, the filter residue is washed once with dilute sulfuric acid (3wt% sulfuric acid solution, solid-liquid ratio 1:5, stirred and washed at 40°C for 30 minutes). The rest of the process is the same as in Example 1.

[0061] Comparative Example 9: This comparative example differs from Example 1 in that it does not include modified γ-polyglutamic acid, modified nano-sepiolite fibers, or FeOOH seeds. The remaining steps and conditions are the same as in Example 1.

[0062] Experimental Example 1: The S3 treatment liquid 2 obtained from Examples 1-3 and Comparative Examples 1-9 was filtered by pressure, and the Fe and Cr contents in the filtrate and filter residue were determined. The iron removal rate and the total chromium recovery rate were calculated. The results are shown in Table 1.

[0063] Take 2 leachate and the chromium recovery solution obtained in step S4 (including the Cr recovered from the supplementary pickling solution in Comparative Example 8) respectively, and determine the Cr by ICP-OES. 3+ 1. Total Fe concentration (sample dissolved in hydrochloric acid before analysis). Iron removal rate = (Total Fe in leachate 2 - Total Fe in filtrate of treated solution 2) / Total Fe in leachate 2 × 100%; Total chromium recovery rate = Cr in chromium recovery solution 3+ Total amount / Cr in leachate 23+ Total amount × 100%. Each group was prepared independently in 3 replicates, and each batch was measured in parallel 3 times.

[0064] Table 1. Results of iron removal rate and total chromium recovery rate for each group:

[0065]

[0066] Experimental Example 2: The FeOOH grain size and chromium occurrence morphology of the filter residue obtained in Experimental Example 1 (Comparative Example 8 is the filter residue after supplemental acid washing) were characterized to verify the two suppression pathways of bulk phase chelation locking and interface crystal plane regulation; the results are shown in Table 2.

[0067] After washing with distilled water and vacuum drying at 40℃, part of the filter residue was determined by XRD (Cu Kα), and the characteristic diffraction peak (110) was taken. The average grain size of FeOOH was calculated according to the Scherrer formula. The other part was selectively extracted using the modified Tamm method: 0.2 mol / L acidic ammonium oxalate solution (pH 3.25) was used for shaking extraction in a dark room at 25℃ for 2 hours to dissolve the surface adsorbed and weakly crystalline components. The Cr content in the extract was recorded as "surface adsorbed chromium loss rate". The residue was completely digested with aqua regia and the residual Cr was measured and recorded as "lattice solid solution chromium loss rate" (this component did not desorb after ammonium oxalate extraction, representing chromium that had entered the FeOOH lattice). Both loss rates were expressed as the percentage of Cr in the leachate. 3+ Calculated as a percentage of the total input. Each group was independently replicated in 3 batches, and each batch was measured in parallel 3 times.

[0068] Table 2. Analysis results of average grain size and chromium occurrence morphology of FeOOH in each group:

[0069]

[0070] Based on the data in Tables 1 and 2, it can be seen that this invention inhibits Cr through two mechanisms: bulk chelation and locking, and solid-liquid interface crystal plane regulation, respectively, by modifying γ-polyglutamic acid and modifying nano-sepiolite fibers. 3+ Coprecipitation loss, modified γ-polyglutamic acid removes Cr before iron removal 3+ It is transformed into a kinetically stable soluble complex, thereby reducing the amount of free Cr entering the iron removal system at the source. 3+ Modified nano-sepiolite fibers inhibit the growth rate of FeOOH crystals and reduce surface active adsorption sites, thereby reducing the free Cr content. 3+ By forming an interface interception, the two work together to solve the problem of low total chromium recovery rate caused by chromium co-precipitation loss in the existing goethite iron removal process.

[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for separating and recovering chromium from chromium-containing dust collected during chromium smelting, characterized in that, Includes the following steps: S1. Sulfuric acid leaching and reduction: Mix chromium dust collected from chromium smelting with 20-30 wt% sulfuric acid solution at a solid-liquid ratio of 1:4-8 (unit: g / mL). Leach at 85-95℃ for 2-4 hours. After leaching, filter while hot to obtain leachate 1. Add 30-32 wt% NaOH solution to leachate 1 to adjust the pH to 2.0-3.0, then add a reducing agent and react at 40-60℃ for 0.5-1 hours to obtain leachate 2. S2, Chelation pretreatment: Add modified γ-polyglutamic acid to leachate 2 and stir the reaction at 60-80℃ for 3-5 hours to obtain treatment solution 1; S3. Iron removal by oxidation: Add 25-35 wt% hydrogen peroxide solution to treatment solution 1 and react at 35-40℃ for 0.5-1 hour to obtain an oxidizing solution; heat the oxidizing solution to 60-80℃, add modified nano-sepiolite fiber, stir for 10-30 minutes, then add a neutralizing agent at a rate of 0.5-1.0 mL / min, adjust the pH to 3.0-4.0, and react at 60-80℃ for 1.5-2 hours to obtain treatment solution 2. S4. Complex Removal and Recovery: Filter the treated liquid 2 to obtain filter residue and filtrate. Add 90-98 wt% sulfuric acid to the filtrate to adjust the pH to less than 1. Transfer the filtrate to a sealed, pressure-resistant container and maintain the temperature at 130-150℃ for 1-2 hours to obtain a product containing free Cr. 3+ Chromium recovery solution.

2. The method for separating and recovering chromium from chromium-containing dust collected during chromium smelting according to claim 1, characterized in that, In step S1, the Cr in the leachate 1 3+ Concentration of 20-35 g / L, Fe 2+ Concentration of 5-15 g / L, Fe 3+ The concentration is 2-8 g / L; the Cr in the leachate 2 3+ Concentration of 20-35 g / L, Fe 2+ Concentration of 7-22 g / L, Fe 3+ Concentration less than 0.5 g / L.

3. The method for separating and recovering chromium from chromium-containing dust collected during chromium smelting according to claim 1, characterized in that, The reducing agent mentioned in step S1 is ascorbic acid, and the amount added is 4-20 g / L.

4. The method for separating and recovering chromium from chromium-containing dust collected during chromium smelting according to claim 1, characterized in that, The preparation method of the modified γ-polyglutamic acid includes the following steps: A1. Dissolve γ-polyglutamic acid in deionized water, adjust the pH to 6-7 with 5wt% NaOH solution, add EDC hydrochloride, stir at room temperature to obtain an activation solution, add the activation solution dropwise to 5-10wt% ethylenediamine aqueous solution under ice bath conditions of 0-5℃, dialyze to remove unreacted ethylenediamine after the reaction is complete to obtain an intermediate solution; A2. Adjust the pH of the intermediate solution obtained in step A1 to 9-10 with 5wt% NaOH solution, add chloroacetic acid, and react at 50-60℃ for 4-6 hours. After the reaction is completed, dialyze the reaction solution with deionized water to obtain an iminodiacetic acid-grafted γ-polyglutamic acid solution. A3. The pH of the iminodiacetic acid-grafted γ-polyglutamic acid solution obtained in step A2 was adjusted to 6-7 with 5wt% NaOH solution. EDC hydrochloride and NHS were added, followed by amino-polyethylene glycol. The mixture was stirred and reacted at room temperature, dialyzed, and freeze-dried to obtain modified γ-polyglutamic acid.

5. The method for separating and recovering chromium from chromium-containing dust collected during chromium smelting according to claim 1, characterized in that, The preparation method of the modified nano-sepiolite fiber includes the following steps: B1. Nano-sized sepiolite fibers with a diameter of 20-50 nm were vacuum dried at 120 °C for 12 hours. After being removed, they were dispersed in anhydrous toluene, and diethylphosphonoethyltriethoxysilane was added. The mixture was refluxed at 80 °C for 8-12 hours under nitrogen protection. After centrifugation, the supernatant was discarded, and the mixture was washed with toluene and ethanol in sequence. After ultrasonic dispersion, it was centrifuged again to obtain diethylphosphonate-grafted sepiolite. B2. Disperse the diethyl phosphonate-grafted sepiolite obtained in step B1 in dichloromethane, add trimethylsilane bromide, stir the reaction at room temperature, remove the solvent by rotary evaporation after the reaction is completed, add anhydrous methanol and continue stirring the reaction, centrifuge, wash and dry to obtain phosphonate-modified sepiolite. B3. Disperse the phosphonic acid-modified sepiolite obtained in step B2 in anhydrous toluene, add 3-aminopropyltriethoxysilane, reflux at 80°C for 6-8 hours under nitrogen protection, centrifuge, wash, and then disperse in N,N-dimethylformamide, add succinic anhydride, stir and react at room temperature, centrifuge, wash, and dry to obtain modified nano-sepiolite fibers.

6. The method for separating and recovering chromium from chromium-containing dust collected during chromium smelting according to claim 1, characterized in that, The amount of modified γ-polyglutamic acid added in step S2 is 8-12 g / L; the amount of modified nano-sepiolite fiber added in step S3 is 0.8-1.2 g / L.

7. The method for separating and recovering chromium from chromium-containing dust collected during chromium smelting according to claim 1, characterized in that, The neutralizing agent mentioned in step S3 is added dropwise in the form of a slurry with a mass fraction of 10%-20%. The neutralizing agent is lime milk, and the amount added is 20-40 g / L based on Ca(OH)2.

8. The method for separating and recovering chromium from chromium-containing dust collected during chromium smelting according to claim 1, characterized in that, In step S3, FeOOH seed crystals are added before adding the neutralizing agent, and the amount added is 0.05-0.3 g / L.